Leksikon dalam Tradisi Wiwitan di Desa Banyuroto Kabupaten Kulon Progo - Pujianti, Kiki (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2025)
Wiwitan tradition is one of the traditions of the people in Banyuroto Village, Kulon Progo Regency, which is held before the harvest period begins. The wiwitan tradition is a form of gratitude from farmers for the harvest given by God. This research uses descriptive qualitative method. Data collection in this study used interview techniques. The results of the data obtained then analysed using a linguistic approach. The data obtained from the results of interviews with several informants stated that in the wiwitan tradition there are 15 lexicons related to the wiwitan tradition, both objects, processions and names of dishes. From the lexical and cultural meanings, it was found that the function of the lexicon in the wiwitan tradition is to connect to God, to connect to supernatural beings, and as a prayer and life guide for the people of Banyuroto Village, Kulon Progo Regency.